2010
DOI: 10.1177/0898010109360256
|View full text |Cite
|
Sign up to set email alerts
|

Florence Nightingale

Abstract: Although generally recognized as the founder of modern nursing, Florence Nightingale has been criticized for her apparent lack of support of women's issues, including suffrage. This article examines the primary and supporting literature surrounding this topic. Findings indicate that Nightingale developed a complex set of beliefs that supported women as individuals rather than from a gender perspective. She did, in fact, support the concept of women's suffrage but did not give it priority. Victorian women suffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Although this study included perceptions among Christian nursing students in India, the findings have implications for the nursing profession at large, including nonChristian nurses in India. In a critical essay on Florence Nightingale and the social impact of feminist values in nursing, Selanders (2010) emphasized Nightingale's ''conception of nursing as a secular, educated profession'' (p. 70). Nightingale herself was a professed Christian but continually advocated for the principles of the profession to promote the health of individuals and populations through the implementation of scientific methods (Selanders 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this study included perceptions among Christian nursing students in India, the findings have implications for the nursing profession at large, including nonChristian nurses in India. In a critical essay on Florence Nightingale and the social impact of feminist values in nursing, Selanders (2010) emphasized Nightingale's ''conception of nursing as a secular, educated profession'' (p. 70). Nightingale herself was a professed Christian but continually advocated for the principles of the profession to promote the health of individuals and populations through the implementation of scientific methods (Selanders 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In a critical essay on Florence Nightingale and the social impact of feminist values in nursing, Selanders (2010) emphasized Nightingale's ''conception of nursing as a secular, educated profession'' (p. 70). Nightingale herself was a professed Christian but continually advocated for the principles of the profession to promote the health of individuals and populations through the implementation of scientific methods (Selanders 2010). While the origins of nursing in India sprung up through Christian missions (Percot 2006), the perceived meaningful work of nursing including its intrinsic and lifelong rewards is not limited to the Christian nurse.…”
Section: Discussionmentioning
confidence: 99%
“…16 Although it now seems obvious that basic hygiene measures are crucial to the quality of healthcare and patient outcomes, several pioneers made significant contributions swimming against the tide of official policy. Florence Nightingale developed modern nursing during the Crimean war though promoting cleaning of wounds, better food and clean, more spacious hospital wards, 17 reducing mortality to around 2%. Semmelweiss showed that doctors carried germs between patients, often spreading fatal infections that could be prevented by hand washing between patients.…”
Section: -Old Lebanese Proverbmentioning
confidence: 99%